Reform of Russian Education and the New Law on Education of 2012 - Troshkina, Tatyana (Europejskie Stowarzyszenie Studentów Prawa ELSA Poznań, 2014)
The article analyses the innovations of the Law on Education adopted in 2012, which is expected to become the basis for creating modernized education legislation that will allow the needs of the social and economic environment of the XXI century and the obligations engaged by Russia during the process of integration with the European educational space to be met.
Keywords: Education law; sources of education law; legal regulation of relations in the sphere of education; education legislation